Clinical and Demographic Profiling of Patients with Spondyloarthritis and Its Association with Disease Activity in a Tertiary Hospital in Surabaya, Indonesia - Yudha, Cahaya Prasta; Rahmawati, Lita Diah; Indrasari, Yulia Nadar; Yuliasih (Current Internal Medicine Research and Practice Surabaya Journal, 2024)
Introduction: The assessment of disease activity is crucial for effectively managing chronic diseases like spondyloarthritis (SpA). Establishing the relationship between disease activity, demographic, and clinical factors is essential for better disease management. This study aimed to delve into the demographic and clinical characteristics of patients at Dr. Soetomo General Academic Hospital, a tertiary hospital in Surabaya, Indonesia, contributing to a comprehensive understanding of SpA occurrences in Surabaya.Methods: Data were obtained from 38 SpA patients' data classified using ASAS 2009 criteria at Dr. Soetomo General Academic Hospital, excluding individuals with SLE, gout, RA, and septic arthritis. Disease activity was measured using ASDAS-CRP. Association analysis between disease activity, clinical parameters, and demographics was conducted using Mann-Withney U test and Spearman correlation test.Results: Results indicated a male-to-female ratio of 8:30, with patients having a median age of 48 (95% CI: 41-53) and most of the patients had a senior high school education (42.11%). The patients exhibited a mean BMI of 25.19 ± 3.77, a median disease duration of 8.5 (95% CI: 5-10) years, and a median CRP value of 0.2 (95% CI: 0.1-0.5) mg/dL. The majority displayed moderate disease activity, with a median ASDAS-CRP score of 2 (95% CI: 1.5-2.7). Interestingly, no significant correlation was found between disease activity using ASDAS-CRP and the demographic or clinical parameters studied.Conclusion: Disease activities were found not to have correlations with the demography and clinical parameters of patients with SpA from Dr. Soetomo General Academic Hospital in Surabaya, Indonesia. This emphasizes the necessity for further research to comprehend the intricate relationship between disease activity and diverse influencing factors.